Group B Streptococcal Disease in Nonpregnant Patients: Emergence of Highly Resistant Strains of Serotype Ib in Taiwan in 2006 to 2008 - Wang, Ying-Hsiang (American Society for Microbiology (ASM), 2010)
Among the 228 group B Streptococcus (GBS) isolates recovered in 2006 to 2008, higher resistance to erythromycin (58.3%) and clindamycin (57.9%) was found in isolates with certain resistance phenotypes. Serotype Ib isolates (24.6%) were the second most prevalent serotype, next to serotype V (29.4%), and showed the highest resistance rates to erythromycin (91.0%) and clindamycin (82.1%).